A novel synthesis method of degradable trace element water-soluble fertilizer EDDS chelate salt
Patent Information
- Application Number
- CN202611143771.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-30
AI Technical Summary
[0010]本发明的目的在于:解决现有EDDS螯合盐制备方法中高温加工导致EDDS热降解、粉末状产品水溶速率慢且易结块、小分子金属络合物难以控制结晶形貌等的问题
[0023](一)本发明全程最高加工温度不超过70℃,脱水干燥在低于-20℃的冷冻状态下通过升华完成,消除喷雾干燥带来的高温脱羧降解风险。产品中游离EDDS含量≤0.5%,纯度显著提升。
Abstract
Description
Technical Field
[0001] This invention relates to the field of trace element water-soluble fertilizer technology, and more specifically to a method for synthesizing a novel biodegradable trace element water-soluble fertilizer EDDS chelate salt. Background Technology
[0002] Micronutrients such as iron, zinc, manganese, and copper are essential nutrients for plant growth and development, playing irreplaceable roles in physiological processes such as chlorophyll synthesis, photosynthesis, enzyme system activation, and nitrogen metabolism. However, micronutrients are easily fixed in soil—iron ions form insoluble ferric hydroxide precipitates in alkaline soils, while zinc, manganese, and copper ions are adsorbed by soil colloids or form insoluble compounds with carbonates and phosphates, resulting in an actual utilization rate of micronutrients by plants that is generally less than 10%.
[0003] To address this issue, chelation technology has been introduced into the field of micronutrient fertilizers. Chelating agents form stable coordination bonds with metal ions, effectively preventing the fixation of metal ions in the soil and improving their diffusion capacity and plant absorption efficiency. Currently, the most widely used chelating agent is EDTA (ethylenediaminetetraacetic acid). However, EDTA has extremely poor biodegradability, and long-term application leads to its accumulation in the soil year after year, causing not only soil pollution but also potentially activating harmful heavy metals such as lead and cadmium in the soil, posing environmental risks.
[0004] EDDS (ethylenediamine disuccinic acid), as a biodegradable aminopolycarboxylic acid chelating agent, has received considerable attention in the field of environmental protection. Existing technologies disclose several methods for synthesizing chelate salts, involving the heating reaction of ligands and metal compounds in water, adjusting the pH value with alkali, and drying to obtain solid chelate salt products.
[0005] However, the existing methods for preparing EDDS chelate salts have the following significant drawbacks:
[0006] (i) High-temperature processing leads to a decline in product quality. Existing chelate salt synthesis processes often employ high-temperature reactions at 100-120℃ and heating / spray drying. EDDS is highly susceptible to decarboxylation degradation under high-temperature conditions (especially prolonged heating above 80℃), reducing the content of active ingredients.
[0007] (ii) The water solubility rate of powdered products is not ideal. Fine powders prepared using existing processes tend to agglomerate into insoluble "fish-eye" shaped clumps when added to water, requiring several minutes of stirring to dissolve. This easily clogs filters in integrated water and fertilizer drip irrigation systems.
[0008] (iii) Lack of microstructure design in products. Existing chelate salt products are all solid particles or powders in a random aggregate state. The dissolution rate is greatly affected by the particle size distribution, and the batch-to-batch stability is poor.
[0009] Therefore, it is necessary to propose a novel method for synthesizing EDDS chelate salts for biodegradable trace element water-soluble fertilizers to solve the above problems. Summary of the Invention
[0010] The purpose of this invention is to solve the problems in existing EDDS chelate salt preparation methods, such as high-temperature processing leading to EDDS thermal degradation, slow water solubility and easy agglomeration of powdered products, and difficulty in controlling the crystal morphology of small molecule metal complexes.
[0011] To achieve the above objectives, the present invention specifically adopts the following technical solution:
[0012] A novel method for synthesizing EDDS chelate salts for biodegradable water-soluble fertilizers containing trace elements.
[0013] The steps include: (1) dissolving ethylenediamine disuccinic acid (EDDS) in water, adding a soluble metal salt, and carrying out a chelation reaction at 50-70°C to obtain an EDDS-metal complex solution;
[0014] (2) Add an ice crystal growth regulator to the solution obtained in step (1), wherein the ice crystal growth regulator is polyvinyl alcohol or hydroxyethyl cellulose, and the amount is 0.5%-3% of the mass of EDDS;
[0015] (3) Place the solution obtained in step (2) in a directional freezing device and carry out directional freezing crystallization under a single-direction temperature gradient. The cold end temperature is -20℃ to -50℃ and the freezing time is 2-6 hours. This allows the ice crystals in the solution to grow directionally along the temperature gradient direction, and the EDDS-metal complex precipitates in the gaps between the ice crystals to form a frozen body with a layered structure.
[0016] (4) Freeze-dry the frozen body obtained in step (3) at a temperature of -20°C to -50°C, a vacuum of less than 50 Pa, and a drying time of 12-72 hours. After the ice crystals sublimate, they form oriented layered macroporous channels, thus obtaining EDDS chelate salt with a layered porous structure.
[0017] Furthermore, in step (3), the unidirectional temperature gradient is achieved by controlling the cooling of the cold source at a rate of 1°C / min to 5°C / min. Controlling this specific cooling rate is a key kinetic parameter determining the lateral size of the ice crystals and the pore width of the product.
[0018] Furthermore, in step (2), the ice crystal growth regulator is partially hydrolyzed polyvinyl alcohol with a degree of hydrolysis of 85%-90%; and the temperature at which the regulator is added is 40℃-50℃.
[0019] Furthermore, the cold end temperature of step (3) is -30°C to -35°C; the freeze-drying temperature of step (4) is -30°C to -40°C, and the vacuum degree is less than 20Pa.
[0020] Furthermore, in step (3), the temperature gradient direction is vertical, the bottom of the directional freezing device is a heat-conducting plate that contacts the cold source, and the sidewall is made of heat-insulating material.
[0021] This invention also provides a biodegradable trace element water-soluble fertilizer EDDS chelate salt prepared by the above method. The EDDS chelate salt has a directionally arranged layered porous structure, with the layered channels arranged parallel to the freezing direction, the channel width being 5-50 μm, and the specific surface area being 50-120 m² / g. The pore walls of the layered channels are formed by cross-linking EDDS-metal complexes and the ice crystal growth regulator through a hydrogen bond network.
[0022] Beneficial effects
[0023] (i) The maximum processing temperature of this invention does not exceed 70℃ throughout the entire process, and dehydration and drying are completed by sublimation under a frozen state below -20℃, eliminating the risk of high-temperature decarboxylation degradation caused by spray drying. The free EDDS content in the product is ≤0.5%, and the purity is significantly improved.
[0024] (II) This invention targets EDDS small molecule complexes, employing a cooling rate of 1-5℃ / min in combination with polyvinyl alcohol (PVA) with a degree of alcoholysis of 85%-90%. The hydroxyl groups on the PVA molecular chain can efficiently form a hydrogen bond network with the EDDS complex. This not only constrains the radial growth of ice crystals but also serves as a framework to support the layered pore walls.
[0025] (iii) The directional arrangement of large pores in the product of this invention exhibits a capillary action similar to that of plant vascular bundles. When immersed in water, water molecules instantly penetrate the interior of the particles along the channels, achieving self-sinking within 10 seconds and a dissolution rate of over 90% within 30 seconds. Detailed Implementation
[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.
[0027] I. Description of Experimental Materials and Test Methods
[0028] 1. Experimental materials
[0029] Ethylenediamine disuccinic acid (EDDS): Industrial grade, effective content ≥98%, purchased from commercial sources.
[0030] Polyvinyl alcohol (PVA): PVA-1788 (88% degree of hydrolysis) and PVA-2488 (88% degree of hydrolysis) were used, and were chemically pure.
[0031] Metal salts (FeCl3·6H2O, ZnSO4·7H2O, etc.): all were analytical grade and purchased from Sinopharm Chemical Reagent Co., Ltd.
[0032] 2. Test methods and instruments
[0033] Microscopic morphology and channel width testing: The cross-sectional morphology of the particles was observed using a field emission scanning electron microscope (SEM, Hitachi SU8010), and the width of the layered channels was measured using image analysis software.
[0034] Specific surface area test: The specific surface area and porosity were determined using a fully automated specific surface area and porosity analyzer (Micromeritics ASAP2460) based on the BET method (N2 physical adsorption).
[0035] Free EDDS content test: High performance liquid chromatography (HPLC, Agilent 1260) was used with a C18 reversed-phase column, a phosphate buffer containing tetrabutylammonium bromide as the mobile phase, and a detection wavelength of 240 nm.
[0036] Dissolution rate test: At standard room temperature of 25℃, 100mL of deionized water was measured into a beaker. 1.0g of the prepared EDDS chelate salt particles were added, and the mixture was magnetically stirred at a constant speed of 150r / min. The change in solution conductivity was monitored in real time using an online conductivity meter. The time required for the conductivity to reach 90% of the final stable value was recorded, which is the 90% dissolution time.
[0037] Biodegradability test: The biodegradability test was conducted in strict accordance with the OECD 301B standard (CO2 generation method) for 28 days.
[0038] II. Implementation Examples
[0039] Example 1: Optimal preparation process of EDDS chelated iron (1) Complexation reaction:
[0040] In a 1000mL three-necked flask equipped with a mechanical stirrer, add 500g of deionized water and 100g of EDDS, and start stirring at 250 rpm. Then slowly add 48g of ferric chloride hexahydrate. Raise the water bath temperature to 60°C and maintain the temperature with stirring for 45 minutes.
[0041] During the reaction, the solution color was observed to gradually change from a light yellow turbid liquid to a dark reddish-brown (amber). After the reaction was completed, 8% ammonia solution was added dropwise at a rate of 2 mL / min using a constant flow titration pump to precisely adjust the pH of the solution to 6.8, resulting in a clear solution of the EDDS-Fe complex.
[0042] (2) Add regulator: When the above solution cools down to 45°C, add 1g PVA-1788 (1% of the mass of EDDS), and stir continuously for 30 minutes until PVA is completely dissolved and there are no visible particles in the solution.
[0043] (3) Directional Freezing Crystallization: The solution is injected into a custom-made directional freezing mold to a height of approximately 30 mm. The mold's sidewalls are constructed of polytetrafluoroethylene (PTFE) and an outer layer of polyurethane foam, with a 5 mm thick copper heat-conducting plate at the bottom. The bottom of the copper plate is brought into close contact with a programmable temperature-controlled liquid nitrogen cooling stage. The temperature control program is activated, and the cooling rate is set to 2 °C / min, allowing the temperature of the cold-end copper plate to steadily decrease from room temperature to -30 °C. Ice crystals can be observed to propagate vertically from the bottom upwards in a columnar pattern. Once the temperature reaches -30 °C, it is maintained at a constant temperature for a total freezing time of 4 hours, resulting in a fully solidified layered frozen body.
[0044] (4) Freeze-drying and post-processing: Demold the frozen body and quickly transfer it to a freeze dryer (ChristAlpha 2-4 LSCplus). Set the partition temperature to -35℃ and the vacuum degree to 15Pa, and continuously sublimate for 36 hours. Remove the dried porous solid block and mechanically crush it at low speed using a roller crusher. Collect irregular particles with a particle size between 0.5-3mm through a standard sieve to obtain the finished product.
[0045] Example 2: Preparation of EDDS-chelated zinc using hydroxyethyl cellulose
[0046] (1) Dissolve 100g of EDDS in 500g of water at 300r / min. Add 51g of zinc sulfate heptahydrate and react at 60℃ for 45 minutes. Adjust the pH to 7.2 with ammonia water to obtain an EDDS-Zn complex solution.
[0047] (2) Cool down to 50°C, add 1.5g of hydroxyethyl cellulose (HEC), the amount is 1.5%, stir until completely dissolved and observe a slight increase in the viscosity of the solution.
[0048] (3) The solution was injected into the directional freezing mold, and the cooling rate was set to 3.0℃ / min to rapidly reduce the temperature of the bottom plate to -35℃ and freeze at a constant temperature for 3.5 hours. The faster cooling rate allowed the ice crystal growth interface to advance more quickly.
[0049] (4) In a freeze dryer, set the temperature to -40℃ and the vacuum degree to 10Pa, and dry for 48 hours. Crush and screen to collect 0.5-3mm particles.
[0050] Example 3: Exploring the lower limit of process parameters—Preparation of EDDS chelated manganese from rapid freezing and high-concentration PVA
[0051] (1) Dissolve 100g of EDDS in 450g of water. Add 33g of manganese sulfate monohydrate, react at 50℃ for 60 minutes, and adjust the pH to 7.5 with ammonia.
[0052] (2) Add 3.0g PVA-1788 at 40℃, which is the upper limit of 3%, and stir to dissolve.
[0053] (3) In order to obtain extremely fine microchannels, rapid cooling is adopted: the cooling rate is set to 5.0℃ / min, the temperature of the substrate is reduced to -50℃, and the substrate is frozen at a constant temperature for 2 hours.
[0054] (4) Transfer to a freeze dryer, set the temperature to -50℃ and the vacuum degree to 5Pa, and dry for 24 hours. Crush and sieve to collect 0.5-3mm particles. Due to the extremely rapid cooling and the strong hydrogen bond inhibition effect of the high concentration of PVA, the ice crystals are extremely fine.
[0055] Example 4: Exploring the upper limit of process parameters—Slow freezing to prepare EDDS chelated copper
[0056] (1) Dissolve 100g of EDDS in 550g of water. Add 45g of copper sulfate pentahydrate, react at 70℃ for 30 minutes, and adjust the pH to 6.5 with ammonia.
[0057] (2) At 50°C, add 0.5g PVA-2488, which is the lower limit of 0.5%, and stir to dissolve.
[0058] (3) Use slow cooling to obtain large aperture: Set the cooling rate to 1.0℃ / min, so that the temperature of the bottom plate drops to -20℃ and is kept at a constant temperature for 6 hours.
[0059] (4) In a freeze dryer, set the temperature to -20℃ and the vacuum degree to 45Pa, and slowly sublimate and dry for 72 hours. Crush and sieve to collect 0.5-3mm particles.
[0060] III. Comparative Example
[0061] Comparative Example 1: A clear solution of EDDS-Fe complex was prepared using the existing high-temperature spray drying method, similar to Example 1. Subsequently, without freezing, the solution was directly pumped into a centrifugal spray dryer. The inlet air temperature was set to 180°C, the outlet air temperature to 90°C, and the feed rate to 15 mL / min. The fine powder at the bottom of the drying tower was collected. Testing revealed that the powder particles were small but solid, and upon being added to water, they quickly formed viscous, fish-eye-like agglomerates on the surface, hindering internal dissolution.
[0062] Comparative Example 2: Without an ice crystal growth regulator, the process was performed under exactly the same conditions as in Example 1, except that no PVA or HEC regulator was added in step (2). After demolding and freeze-drying, the dried block was observed to be extremely brittle, crumbling upon slight touch. SEM observation showed that although traces of some layered structures were present internally, large areas of the pore walls collapsed and fractured, failing to form continuous capillary channels. This demonstrates that small molecule complexes, lacking the hydrogen bond crosslinking support of a polymer regulator, cannot resist the capillary contraction force during sublimation drying.
[0063] Comparative Example 3: Non-directional isotropic freezing. A solution containing 1% PVA was prepared according to Example 1. The solution was poured into a regular plastic beaker and placed directly into a commercial ultra-low temperature freezer at -30°C for isotropic freezing, with simultaneous cooling on all four sides. After freezing, the same freeze-drying process was performed. SEM morphology showed that the product had a disordered equiaxed porous structure, with not only varying pore sizes but also a large number of dead pores. In the dissolution test, water molecules could not quickly penetrate into the particles, and the 10-second self-sinking wetting phenomenon observed in Example 1 was not exhibited.
[0064] IV. Summary and Comparison of Performance Test Results
[0065] The products prepared in Examples 1-4 and Comparative Examples 1-3 were tested in a unified manner, and the results are detailed in the table below:
[0066] Example 1 0.25% Continuous parallel layered structure, 10-25 μm 105 22 seconds 88% Example 2 0.38% Continuous parallel layered structure, 15-35 μm 90 28 seconds 85% Example 3 0.22% Continuous parallel dense layered structure, 5-12 μm 118 18 seconds 92% Example 4 0.45% Continuous, parallel, broad, layered structure, 30-50 μm 65 35 seconds 78% Comparative Example 1 5.20% Random solid particles, without channels 12 240 seconds (severe clumping) 82% Comparative Example 2 0.30% Localized layered but severely collapsed and fractured 35 85 seconds 87% Comparative Example 3 0.28% Disorganized equiaxial holes, many dead holes 45 110 seconds 88%
[0067] Results analysis:
[0068] 1. As shown in the table, Examples 1-4 utilize the capillary self-wetting effect brought about by directional layered channels, achieving a dissolution time of 18-35 seconds, which is nearly 1 / 10 of the 240 seconds for conventional powder in Comparative Example 1. Comparative Examples 2 and 3 demonstrate that without directional freezing or regulating agents, effective microchannels cannot be formed, resulting in slower dissolution.
[0069] 2. The free EDDS content in Examples 1-4 and the freeze-dried comparative example was ≤0.45%, while that in the spray-dried comparative example 1 was as high as 5.20%, which proves the absolute advantage of the whole-process low-temperature freeze-drying process of the present invention in protecting the molecular structure of EDDS.
[0070] 3. Example 3 yielded the narrowest channel and the largest specific surface area; Example 4 yielded the widest channel. This demonstrates that the process parameters provided by this invention can stably and precisely control the microstructure of the product.
[0071] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. The scope of patent protection of the present invention shall be determined by the claims. Similarly, any equivalent structural changes made based on the content of the present invention's specification shall also be included within the scope of protection of the present invention.
Claims
1. A method for synthesizing a novel biodegradable trace element water-soluble fertilizer EDDS chelate salt, characterized in that, Includes the following steps: (1) Dissolve ethylenediamine disuccinic acid (EDDS) in water, add a soluble metal salt, and carry out a chelation reaction at 50-70℃ to obtain an EDDS-metal complex solution; (2) Add an ice crystal growth regulator to the solution obtained in step (1), wherein the ice crystal growth regulator is polyvinyl alcohol or hydroxyethyl cellulose, and the amount is 0.5%-3% of the mass of EDDS; (3) Place the solution obtained in step (2) in a directional freezing device and carry out directional freezing crystallization under a single-direction temperature gradient. The cold end temperature is -20℃ to -50℃ and the freezing time is 2-6 hours. This allows the ice crystals in the solution to grow directionally along the temperature gradient direction, and the EDDS-metal complex precipitates in the gaps between the ice crystals to form a frozen body with a layered structure. (4) Freeze-dry the frozen body obtained in step (3) at a temperature of -20°C to -50°C, a vacuum of less than 50 Pa, and a drying time of 12-72 hours. After the ice crystals sublimate, they form oriented layered macroporous channels, thus obtaining EDDS chelate salt with a layered porous structure.
2. The method for synthesizing the novel biodegradable trace element water-soluble fertilizer EDDS chelate salt according to claim 1, characterized in that, In step (3), the unidirectional temperature gradient is achieved by controlling the cooling of the cold source, and the cooling rate is 1℃ / min to 5℃ / min.
3. The method for synthesizing the novel biodegradable trace element water-soluble fertilizer EDDS chelate salt according to claim 1 or 2, characterized in that, In step (2), the ice crystal growth regulator is partially hydrolyzed polyvinyl alcohol with a degree of hydrolysis of 85%-90%; and the temperature at which the regulator is added is 40℃-50℃.
4. The method for synthesizing the novel biodegradable trace element water-soluble fertilizer EDDS chelate salt according to claim 1, characterized in that, The soluble metal salt is selected from any one of iron salts, zinc salts, manganese salts, and copper salts; Preferably, the iron salt is selected from at least one of ferric chloride, ferric sulfate, ferric nitrate, and ferric ammonium sulfate; The zinc salt is selected from at least one of zinc sulfate, zinc chloride, and zinc nitrate; The manganese salt is selected from at least one of manganese sulfate, manganese chloride, and manganese nitrate; The copper salt is selected from at least one of copper sulfate, copper chloride, and copper nitrate.
5. The method for synthesizing the novel biodegradable trace element water-soluble fertilizer EDDS chelate salt according to claim 1, characterized in that, The molar ratio of EDDS to the metal element in the soluble metal salt is 1:0.95-1.1; the mass ratio of EDDS to water in step (1) is 1:4.5-5.5, the pH of the chelation reaction is 6.5-7.5, and the reaction time is 30-60 minutes.
6. The method for synthesizing the novel biodegradable trace element water-soluble fertilizer EDDS chelate salt according to claim 1, characterized in that, The cold end temperature of step (3) is -30℃ to -35℃; the freeze-drying temperature of step (4) is -30℃ to -40℃, and the vacuum degree is less than 20Pa.
7. The method for synthesizing the novel biodegradable trace element water-soluble fertilizer EDDS chelate salt according to claim 1, characterized in that, In step (3), the temperature gradient direction is vertical, the bottom of the directional freezing device is a heat-conducting plate that contacts the cold source, and the side wall is an insulating material.
8. The method for synthesizing the novel biodegradable trace element water-soluble fertilizer EDDS chelate salt according to claim 1, characterized in that, Step (4) is followed by a crushing and screening step to collect particles with a diameter of 0.5-3 mm.
9. The method for synthesizing the novel biodegradable trace element water-soluble fertilizer EDDS chelate salt according to claim 1, characterized in that, The EDDS chelate salt synthesized by the method has a directionally arranged layered porous structure, with the layered channels arranged parallel to the freezing direction, a channel width of 5-50 μm, and a specific surface area of 50-120 m². 2 / g; The pore walls of the layered channels are formed by cross-linking EDDS-metal complex and the ice crystal growth regulator through a hydrogen bond network.
10. The method for synthesizing the novel biodegradable trace element water-soluble fertilizer EDDS chelate salt according to claim 9, characterized in that, The EDDS chelate salt has a water solubility of over 90% within 30 seconds; the free EDDS content in the EDDS chelate salt does not exceed 0.5%.
